(Meth)acrylic acid copolymer

A (meth)acrylic acid-based copolymer with specific structural units and molecular weight effectively inhibits silica scale in geothermal power generation and industrial cooling water systems.

JP7605865B2Active Publication Date: 2024-12-24NIPPON SHOKUBAI CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022575520
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-15
Filing Date
2021-12-28
Publication Date
2024-12-24
Estimated Expiration
2041-12-28

AI Technical Summary

Technical Problem

Existing scale inhibitors do not effectively address silica scale formation in geothermal power generation and industrial cooling water systems.

Method used

A (meth)acrylic acid-based copolymer containing structural units derived from (meth)acrylic acid, sulfonic acid (salt) group-containing monomers, and ether bond-containing monomers, with specific ratios and molecular weights to enhance silica scale inhibition.

Benefits of technology

The copolymer exhibits excellent ability to suppress silica scale, making it suitable as a silica scale inhibitor in water treatment applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605865000001
    Figure 0007605865000001
  • Figure 0007605865000002
    Figure 0007605865000002
  • Figure 0007605865000003
    Figure 0007605865000003
Patent Text Reader

Abstract

The purpose of the present invention is to provide a (meth)acrylic acid copolymer that can, for example, be used suitably as a silica scale inhibitor due to having a superior ability to inhibit silica scale than in the past. The present invention is a (meth)acrylic acid copolymer including structural units derived from a (meth)acrylic acid (salt), structural units derived from a sulfonic-acid-(salt)-group-containing monomer, and structural units derived from an ether-bond-containing monomer, the content ratio of structural units derived from a sulfonic-acid-(salt)-group-containing monomer being 25 mass% or greater relative to 100 mass% of all structural units, and the weight-average molecular weight of the copolymer being 30,000 or greater.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a (meth)acrylic acid-based copolymer, and more particularly to a (meth)acrylic acid-based copolymer used for inhibiting scale such as silica scale. [Background technology]

[0002] For example, in geothermal power generation, industrial cooling water, and seawater desalination, the generation of scale such as calcium carbonate and silica can be a problem.

[0003] For example, the copolymer described in Patent Document 1 improves the dispersibility of hydrophobic particles and also exhibits excellent chelating ability for calcium ions, making it possible to exhibit extremely good scale prevention ability for the piping and inside of geothermal power generation equipment, and it is disclosed that it can be suitably used as a scale inhibitor for geothermal power generation equipment. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-64382 A Summary of the Invention [Problem to be solved by the invention]

[0005] As mentioned above, various scale inhibitors have been proposed, but there has been a demand for further improvement in the ability to inhibit silica scale. Therefore, an object of the present invention is to provide a (meth)acrylic acid-based copolymer that has excellent silica scale inhibition capability and can therefore be suitably used, for example, as a silica scale inhibitor. [Means for solving the problem]

[0006] The present inventors have conducted various investigations in order to achieve the above-mentioned object, and have found that in a polymer having structural units derived from (meth)acrylic acid (salt), a sulfonic acid (salt) group-containing monomer, and an ether bond-containing monomer, by setting the proportion of structural units derived from the sulfonic acid (salt) group-containing monomer and the weight average molecular weight to be equal to or greater than a predetermined amount, excellent silica scale inhibition ability can be achieved, and have arrived at the present invention. That is, the (meth)acrylic acid-based copolymer of the present disclosure is a copolymer containing structural units derived from (meth)acrylic acid (salt), structural units derived from a sulfonic acid (salt) group-containing monomer, and structural units derived from an ether bond-containing monomer, in which the content of structural units derived from the sulfonic acid (salt) group-containing monomer relative to 100% by mass of all structural units is 25% by mass or more, and the weight average molecular weight of the copolymer is 30,000 or more.

[0007] The structural unit derived from the ether bond-containing monomer is preferably a structural unit derived from a monomer represented by the following general formula (1).

[0008] [ka]

[0009] (In the above general formula (1), R 0 R represents a hydrogen atom or a methyl group. 1 represents a CH2 group, a CH2CH2 group, or a direct bond. Either X or Y represents a hydroxyl group, and the other represents a group represented by the following general formula (2) or a group represented by the following general formula (3).

[0010] [ka]

[0011] (In the above general formulas (2) and (3), R 2 are the same or different and each represents an alkylene group having 2 to 4 carbon atoms. n represents an oxyalkylene group (-OR 2 R is the average number of moles of 0 to 5. 3, R 4 , R 5 each independently represents an alkyl group having 1 to 20 carbon atoms.

[0012] It is preferable that either X or Y in the above general formula (1) is a group represented by the above general formula (2).

[0013] The structural unit derived from the sulfonic acid (salt) group-containing monomer is represented by the following general formula (4);

[0014] [ka]

[0015] (In the formula, R 6 R represents a hydrogen atom or a methyl group. 7 R represents a CH2 group, a CH2CH2 group or a direct bond. 8 , R 9 represents a hydroxyl group or -SO3Z, where Z represents a hydrogen atom, a metal atom, an ammonium group, or an organic amine group. 8 , R 9 one of which represents -SO3Z, and the other represents a hydroxyl group.

[0016] The structural unit derived from the sulfonic acid (salt) group-containing monomer is preferably a structural unit derived from 3-allyloxy-2-hydroxypropanesulfonic acid or a salt thereof.

[0017] The content of the structural units derived from the (meth)acrylic acid (salt) is preferably 15% by mass or more and 74.5% by mass or less, based on 100% by mass of all structural units.

[0018] The content of the structural units derived from the (meth)acrylic acid (salt) is preferably 30% by mass or more and 73% by mass or less, based on 100% by mass of all structural units.

[0019] The content of the structural units derived from the (meth)acrylic acid (salt) is preferably 35% by mass or more and 70% by mass or less, based on 100% by mass of all structural units.

[0020] The content of the structural units derived from the sulfonic acid (salt) group-containing monomer is preferably 25% by mass or more and 60% by mass or less with respect to 100% by mass of all structural units.

[0021] The content of the structural units derived from the sulfonic acid (salt) group-containing monomer is preferably 25% by mass or more and 50% by mass or less with respect to 100% by mass of all structural units.

[0022] The content of the structural units derived from the sulfonic acid (salt) group-containing monomer is preferably 25% by mass or more and 45% by mass or less with respect to 100% by mass of all structural units.

[0023] The content of the structural units derived from the ether bond-containing monomer is preferably 0.5% by mass or more and 30% by mass or less with respect to 100% by mass of all structural units.

[0024] The content of the structural units derived from the ether bond-containing monomer is preferably 1% by mass or more and 25% by mass or less with respect to 100% by mass of all structural units.

[0025] The content of the structural units derived from the ether bond-containing monomer is preferably 1.5% by mass or more and 20% by mass or less with respect to 100% by mass of all structural units.

[0026] The (meth)acrylic acid copolymer preferably has a weight average molecular weight of 30,000 or more and 200,000 or less.

[0027] The (meth)acrylic acid copolymer preferably has a weight average molecular weight of 30,000 or more and 150,000 or less.

[0028] The (meth)acrylic acid copolymer preferably has a weight average molecular weight of 30,000 or more and 100,000 or less.

[0029] The (meth)acrylic acid copolymer preferably has a weight average molecular weight of 30,000 or more and 80,000 or less.

[0030] The present invention also relates to a water treatment agent containing the above (meth)acrylic acid-based copolymer.

[0031] The present invention also relates to a scale inhibitor containing the above-mentioned (meth)acrylic acid-based copolymer.

[0032] The present invention further relates to a silica scale inhibitor containing the above-mentioned (meth)acrylic acid-based copolymer. Effect of the Invention

[0033] The (meth)acrylic acid-based copolymer of the present disclosure exhibits a good ability to inhibit silica components, etc. Therefore, the (meth)acrylic acid-based copolymer of the present disclosure can be preferably used as a water treatment agent for inhibiting scale such as silica scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] The present invention will be described in detail below. In addition, a combination of two or more of the individual preferred embodiments of the present invention described below is also a preferred embodiment of the present invention.

[0035] [(Meth)acrylic acid-based copolymer of the present disclosure] The (meth)acrylic acid-based copolymer of the present disclosure includes a copolymer containing structural units derived from (meth)acrylic acid (salt), structural units derived from a sulfonic acid (salt) group-containing monomer, and structural units of an ether bond-containing monomer, in which the content of structural units derived from the sulfonic acid (salt) group-containing monomer relative to 100% by mass of all structural units is 25% by mass or more, and the weight average molecular weight of the copolymer is 30000 or more. The above copolymer is also referred to as the "copolymer of the present disclosure."

[0036] <Structural unit derived from (meth)acrylic acid (salt)> In the present disclosure, (meth)acrylic acid (salt) refers to acrylic acid, methacrylic acid, and salts thereof. The above salt is not particularly limited, but examples thereof include alkali metal salts, alkaline earth metal salts, transition metal salts, and ammonium salts. In the present disclosure, the structural unit derived from (meth)acrylic acid (salt) refers to a structural unit in which the carbon-carbon double bond of (meth)acrylic acid (salt) is replaced with a carbon-carbon single bond. For example, if acrylic acid is CH2=CH(COOH), the structural unit derived from acrylic acid can be represented as -CH2-CH(COOH)-. The structural unit derived from (meth)acrylic acid (salt) can be formed, for example, by radical polymerization of (meth)acrylic acid (salt). Note that the structural unit derived from (meth)acrylic acid (salt) is not limited to a structural unit formed by polymerization of (meth)acrylic acid (salt), as long as it has the same structure as the structure in which the carbon-carbon double bond of (meth)acrylic acid (salt) is replaced with a carbon-carbon single bond, and may be, for example, a structural unit formed by a post-reaction after polymerization.

[0037] The content of the structural unit derived from (meth)acrylic acid (salt) in the copolymer of the present disclosure is preferably 15% by mass or more and less than 75% by mass, more preferably 30% by mass or more and 74.5% by mass or less, even more preferably 35% by mass or more and 73% by mass or less, even more preferably 40% by mass or more and 70% by mass or less, and particularly preferably 50% by mass or more and 65% by mass or less, based on 100% by mass of the structural units derived from all monomers constituting the copolymer of the present disclosure (hereinafter also referred to as all structural units). The content of the structural unit derived from the (meth)acrylic acid (salt) is calculated in terms of (meth)acrylic acid. The term "in terms of (meth)acrylic acid" means that even if the structural unit derived from (meth)acrylic acid (salt) is a structural unit derived from a (meth)acrylic acid salt, the mass is calculated as (meth)acrylic acid. By being in the above range, the scale inhibitor of the present disclosure tends to have improved scale inhibition ability.

[0038] <Structural unit derived from monomer containing sulfonic acid (salt) group> In the present disclosure, a sulfonic acid (salt) group-containing monomer refers to a compound that contains at least one carbon-carbon double bond and a sulfonic acid (salt) group. The at least one carbon-carbon double bond is usually radically polymerizable. The above salt is not particularly limited, but examples thereof include alkali metal salts, alkaline earth metal salts, transition metal salts, and ammonium salts. In the present disclosure, the structural unit derived from a sulfonic acid (salt) group-containing monomer refers to a structural unit in which at least one carbon-carbon double bond of a sulfonic acid (salt) group-containing monomer is replaced with a carbon-carbon single bond. Note that the structural unit derived from a sulfonic acid (salt) group-containing monomer may have the same structure as the structure in which at least one carbon-carbon double bond of a sulfonic acid (salt) group-containing monomer is replaced with a carbon-carbon single bond, and is not limited to a structural unit formed by polymerization of a sulfonic acid (salt) group-containing monomer, and may be, for example, a structural unit formed by a post-reaction after polymerization.

[0039] The content of the structural unit derived from the sulfonic acid (salt) group-containing monomer in the copolymer of the present disclosure is 25% by mass or more and 60% by mass or less, preferably 25% by mass or more and 50% by mass or less, more preferably 25% by mass or more and 45% by mass or less, even more preferably 27% by mass or more and 43% by mass or less, and particularly preferably 30% by mass or more and 42% by mass or less, based on 100% by mass of the structural units derived from all the monomers constituting the copolymer of the present disclosure. The content of the structural unit derived from the sulfonic acid (salt) group-containing monomer is calculated in terms of sodium salt. The calculation in terms of sodium salt means that even if the sulfonic acid (salt) group contained in the structural unit derived from the sulfonic acid (salt) group-containing monomer is, for example, an acid-type sulfonic acid group, the mass is calculated as the sodium salt of the sulfonic acid group. By being in the above range, the scale inhibitor of the present disclosure tends to have improved scale inhibition ability.

[0040] Specific examples of sulfonic acid (salt) group-containing monomers include vinyl sulfonic acid, styrene sulfonic acid, (meth)allyl sulfonic acid, 3-(meth)allyloxy-2-hydroxypropanesulfonic acid, 3-(meth)allyloxy-1-hydroxypropanesulfonic acid, 2-(meth)allyloxyethylenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, α-methyl-p-styrenesulfonic acid, vinylsulfamic acid, isoprene sulfonic acid, 4-(allyloxy) Examples of the sulfonic acid include benzenesulfonic acid, 1-methyl-2-propene-1-sulfonic acid, 1,1-dimethyl-2-propene-1-sulfonic acid, 3-butene-1-sulfonic acid, 1-butene-3-sulfonic acid, 2-acrylamido-1-methylpropanesulfonic acid, 2-acrylamidopropanesulfonic acid, 2-acrylamido-n-butanesulfonic acid, 2-acrylamido-2-phenylpropanesulfonic acid, 2-((meth)acryloyloxy)ethanesulfonic acid, and salts thereof. Examples of the sulfonic acid (salt) group-containing monomer include those represented by the following formula (4):

[0041] [ka]

[0042] (In the formula, R 6 R represents a hydrogen atom or a methyl group. 7 R represents a CH2 group, a CH2CH2 group or a direct bond. 8 , R 9 represents a hydroxyl group or -SO3Z, where Z represents a hydrogen atom, a metal atom, an ammonium group, or an organic amine group. 8 , R 9 one of which represents -SO3Z, and the other represents a hydroxyl group. In the above formula (4), R 7 When R is a direct bond, it is H2C=C(R 6 )-R 2 -O- is H2C=C(R 6 )-O-. In the above formula (3), R 6is preferably a hydrogen atom. 7 is preferably a CH2 group.

[0043] The above Z represents a hydrogen atom, a metal atom, an ammonium group, or an organic amine group, and when Z represents a metal atom, an ammonium group, or an organic amine group, -SO3Z represents a metal salt, ammonium salt, or organic amine salt of sulfonic acid. Examples of the metal atom in Z include alkali metal atoms such as lithium, sodium, and potassium; alkaline earth metal atoms such as magnesium and calcium; aluminum, iron, and the like. Examples of the organic amine group include alkanolamines such as monoethanolamine, diethanolamine, and triethanolamine; alkylamines such as monoethylamine, diethylamine, and triethylamine; and polyamines such as ethylenediamine and triethylenediamine. Z is preferably a hydrogen atom, an alkali metal atom, or an ammonium group, more preferably a hydrogen atom, sodium, or potassium, and even more preferably a hydrogen atom or sodium.

[0044] Since the scale inhibitory ability of the scale inhibitor of the present disclosure tends to be improved, 3-(meth)allyloxy-2-hydroxypropanesulfonic acid and salts thereof are preferred, and 3-allyloxy-2-hydroxypropanesulfonic acid and sodium salts thereof are more preferred.

[0045] <Structural units derived from ether bond-containing monomers> In the present disclosure, an ether bond-containing monomer refers to a compound containing at least one carbon-carbon double bond and an ether bond. However, since a compound having a sulfonic acid (salt) group is classified as a sulfonic acid (salt) group-containing monomer, even if the sulfonic acid (salt) group-containing monomer is a compound containing an ether bond, it is not included in the ether bond-containing monomer. The at least one carbon-carbon double bond is usually radically polymerizable. In the present disclosure, the structural unit derived from an ether bond-containing monomer refers to a structural unit in which at least one carbon-carbon double bond of an ether bond-containing monomer is replaced with a carbon-carbon single bond. Note that the structural unit derived from an ether bond-containing monomer may have the same structure as the structure in which at least one carbon-carbon double bond of an ether bond-containing monomer is replaced with a carbon-carbon single bond, and is not limited to a structural unit formed by polymerization of an ether bond-containing monomer, and may be, for example, a structural unit formed by a post-reaction after polymerization.

[0046] The content of the structural unit derived from the ether bond-containing monomer in the copolymer of the present disclosure is preferably 0.5% by mass or more and 30% by mass or less, more preferably 1% by mass or more and 25% by mass or less, even more preferably 1.5% by mass or more and 20% by mass or less, even more preferably 2% by mass or more and 15% by mass or less, particularly preferably 2% by mass or more and 10% by mass or less, and most preferably 3% by mass or more and 8% by mass or less, based on 100% by mass of the structural units derived from all the monomers constituting the copolymer of the present disclosure. In addition, when the structural unit derived from the ether bond-containing monomer contains an acid group such as a carboxyl group (salt), the content is calculated in terms of acid. The term "acid equivalent" means that even if the structural unit derived from the monomer contains a salt of an acid group, the mass is calculated as the corresponding acid. The mass of the structural unit derived from the other monomers described later is also calculated in the same manner. By being in the above range, the scale inhibition ability of the scale inhibitor of the present disclosure tends to be improved.

[0047] Examples of ether bond-containing monomers include vinyl ethers such as ethyl vinyl ether, butyl vinyl ether, and benzyl vinyl ether; (meth)allyl ethers such as ethyl methallyl ether, butyl methallyl ether, and benzyl methallyl ether; and isoprenyl ethers such as ethyl isoprenyl ether, butyl isoprenyl ether, and benzyl isoprenyl ether. However, since there is a tendency for scale inhibition ability to be particularly improved, a monomer represented by the following general formula (1) is preferred.

[0048] [ka]

[0049] (In the above general formula (1), R 0 R represents a hydrogen atom or a methyl group. 1 represents a CH2 group, a CH2CH2 group, or a direct bond. Either X or Y represents a hydroxyl group, and the other represents a group represented by the following general formula (2) or a group represented by the following general formula (3).

[0050] [ka]

[0051] (In the above general formulas (2) and (3), R 2 are the same or different and each represents an alkylene group having 2 to 4 carbon atoms. n represents an oxyalkylene group (-OR 2 R is the average number of moles of 0 to 5. 3 , R 4 , R 5 each independently represents an alkyl group having 1 to 20 carbon atoms.

[0052] In the above general formula (1), H2C=C(R 0 )-R 1 -R 0 is a methyl group, R 1 is a CH2 group, it is a methallyl group; R 0 is a methyl group, R 1 isoprenyl group when R is CH2CH2 group; 0 is a methyl group, R 1 is an isopropenyl group when it is a direct bond; R 0 is a hydrogen atom, R 1 is an allyl group; R 0 is a hydrogen atom, R 1 is a CH2CH2 group, then a butenyl group; R 0 is a hydrogen atom, R 1 When it is a direct bond, it represents a vinyl group. H2C=C(R 0 )-R 1- is preferably an isoprenyl group, a methallyl group, an allyl group, or a vinyl group. From the viewpoint of enhancing the polymerizability, an isoprenyl group, a methallyl group, or an allyl group is more preferable. H2C=C(R 0 )-R 1 More preferably, - is an allyl group.

[0053] The combinations of X and Y include X being a hydroxyl group and Y being a group represented by the above general formula (2); X being a hydroxyl group and Y being a group represented by the above general formula (3); X being a group represented by the above general formula (2) and Y being a hydroxyl group; X being a group represented by the above formula (3) and Y being a hydroxyl group. Preferably, X is a hydroxyl group and Y is a group represented by the above general formula (2); X is a hydroxyl group and Y is a group represented by the above general formula (3), and more preferably, X is a hydroxyl group and Y is a group represented by the above general formula (2).

[0054] R in the above formula (2) and (3) 2 are the same or different and represent an alkylene group having 2 to 4 carbon atoms. Examples of the alkylene group having 2 to 4 carbon atoms include an ethylene group, a propylene group, and a butylene group. From the viewpoint of improving the polymerizability of the ether bond-containing monomer, an alkylene group having 2 to 3 carbon atoms, such as an ethylene group or a propylene group, is preferred. As the alkylene group, one or more types can be used.

[0055] In the above formulas (2) and (3), n is an oxyalkylene group (-OR 2 -) and represents a number from 0 to 5. n is preferably 0 to 4, more preferably 0 to 3, still more preferably 0 to 2, particularly preferably 0 or 1, and most preferably 0.

[0056] R in the above general formulas (2) and (3) 3 , R 4 , R 5 is an alkyl group having 1 to 20 carbon atoms. Since this tends to improve the scale inhibition ability of the scale inhibitor of the present disclosure, R 3 , R 4 , R 5The number of carbon atoms in the alkyl group is more preferably 1 to 12, even more preferably 1 to 8, and most preferably 1 to 4. The alkyl group may be linear or branched, may contain a cyclic structure, and may have a substituent. Examples of the substituent include an alkoxy group, an aryl group, a hydroxyl group, a carboxy group, an amino group, and a heterocyclic group. When the alkyl group has a substituent, the number of the substituents may be one or more, and it is preferable that the number of carbon atoms in the alkyl group including the substituent is within the range of the number of carbon atoms.

[0057] Specific examples of the alkyl group having 1 to 20 carbon atoms include a methyl group, an ethyl group, a n-propyl group, a n-butyl group, a n-pentyl group (amyl group), a n-hexyl group, a n-heptyl group, a n-octyl group, a n-nonyl group, a n-decyl group, a n-undecyl group, a n-dodecyl group, a n-tridecyl group, a n-tetradecyl group, a n-pentadecyl group, a n-hexadecyl group, a n-heptadecyl group, a n-octadecyl group, a n-nonadecyl group, a n-icosyl group, an i-propyl group, a sec-butyl group, an i-butyl group, a t-butyl group, a 1-methylbutyl group, and a 1-ethylpropyl group. Examples of the alkyl group include 2-methylbutyl group, i-amyl group, neopentyl group, 1,2-dimethylpropyl group, 1,1-dimethylpropyl group, t-amyl group, 1,3-dimethylbutyl group, 3,3-dimethylbutyl group, 2-ethylbutyl group, 2-ethyl-2-methylpropyl group, 1-methylheptyl group, 2-ethylhexyl group, 1,5-dimethylhexyl group, t-octyl group, branched nonyl group, decyl group, undecyl group, dodecyl group, tridecyl group, tetradecyl group, pentadecyl group, hexadecyl group, heptadecyl group, stearyl group, and icosyl group.

[0058] The preparation method of the ether bond-containing monomer is not particularly limited, and can be prepared by any suitable method. For example, a simple method can be mentioned in which the epoxy ring of a compound having a carbon-carbon double bond and an epoxy ring is reacted with the hydroxyl group and / or amino group of a compound having an alkyl group having 1 to 20 carbon atoms and the hydroxyl group and / or amino group. The ether bond-containing monomer is preferably a reaction product of a compound having a carbon-carbon double bond and an epoxy ring with a compound having an alkyl group having 1 to 20 carbon atoms and a hydroxyl group and / or an amino group, more preferably a reaction product of a compound having a carbon-carbon double bond and an epoxy ring with a compound having an alkyl group having 1 to 20 carbon atoms and a hydroxyl group.

[0059] Examples of the compound having a carbon-carbon double bond and an epoxy ring include (meth)allyl glycidyl ether and glycidyl vinyl ether.

[0060] Examples of the compound having an alkyl group having 1 to 20 carbon atoms and a hydroxyl group include alkyl alcohols having 1 to 20 carbon atoms, such as methanol, ethanol, isopropanol, n-butanol, t-butanol, pentyl alcohol, hexyl alcohol, heptyl alcohol, octyl alcohol, nonyl alcohol, decyl alcohol, undecyl alcohol, dodecyl alcohol (lauryl alcohol), tridecyl alcohol, tetradecyl alcohol, pentadecyl alcohol, hexadecyl alcohol, heptadecyl alcohol, octadecyl alcohol, nonadecyl alcohol, and icosyl alcohol. Among these, methanol, ethanol, isopropanol, n-butanol, and t-butanol are preferred.

[0061] Examples of the compound having an alkyl group having 1 to 20 carbon atoms and an amino group include dialkylamines having 1 to 20 carbon atoms, such as dimethylamine, ethylamine, ethylmethylamine, di-n-propylamine, di-isopropylamine, di-n-butylamine, dipentylamine, dihexylamine, diheptylamine, dioctylamine, and didodecylamine.

[0062] Examples of the compound having an alkyl group having 1 to 20 carbon atoms, a hydroxyl group and an amino group include alkanolamines having 1 to 20 carbon atoms, such as methylethanolamine, methylisopropanolamine, dimethylethanolamine, diisopropanolamine, diethanolamine, triethanolamine and diethylethanolamine.

[0063] The above reaction may be carried out without a catalyst, or in the presence of an acidic catalyst such as boron trifluoride, or a basic catalyst such as sodium hydroxide or potassium hydroxide.

[0064] <Structural units derived from other monomers> The copolymer of the present disclosure may, if desired, have structural units derived from monomers other than (meth)acrylic acid (salt), structural units derived from sulfonic acid (salt) group-containing monomers, and structural units derived from ether bond-containing monomers (also referred to as structural units derived from other monomers). In the present disclosure, the structural unit derived from another monomer refers to a structural unit in which at least one carbon-carbon double bond of another monomer is replaced with a carbon-carbon single bond. Note that the structural unit derived from another monomer may have the same structure as the structure in which at least one carbon-carbon double bond of the other monomer is replaced with a carbon-carbon single bond, and is not limited to a structural unit formed by polymerization of the other monomer, and may be, for example, a structural unit formed by a post-reaction after polymerization.

[0065] In the copolymer of the present disclosure, the content of structural units derived from other monomers is 0% by mass or more and 15% by mass or less, preferably 0% by mass or more and 10% by mass or less, and more preferably 0% by mass or more and 5% by mass or less, relative to 100% by mass of structural units derived from all monomers constituting the copolymer of the present disclosure.

[0066] Examples of the other monomers include carboxyl group-containing monomers such as maleic acid, itaconic acid, and salts thereof; unsaturated alcohols such as (meth)allyl alcohol and isoprenol, and monomers obtained by adding alkylene oxides thereto; polyalkylene glycol chain-containing monomers such as (meth)acrylic acid esters of alkoxyalkylene glycols; vinyl aromatic monomers having heterocyclic aromatic hydrocarbon groups such as vinylpyridine and vinylimidazole; dialkylaminoalkyl (meth)acrylates such as dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, and dimethylaminopropyl acrylate; dialkylaminoalkyl (meth)acrylamides such as dimethylaminoethyl acrylamide, dimethylaminoethyl methacrylamide, and dimethylaminopropyl acrylamide; allylamines such as diallyl alkylamines and diallyl dimethylamine; and quaternized products thereof. N-vinyl monomers such as N-vinyl formamide, N-vinyl acetamide, N-vinyl-N-methyl formamide, N-vinyl-N-methyl acetamide, and N-vinyl oxazolidone; amide monomers such as (meth)acrylamide, N,N-dimethyl acrylamide, N-isopropyl acrylamide, and t-butyl acrylamide; hydroxyl group-containing monomers such as (meth)allyl alcohol and isoprenol; (meth)acrylic acid alkyl ester monomers such as butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and dodecyl (meth)acrylate; (meth)acrylic acid hydroxyalkyl monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyhexyl (meth)acrylate; vinyl aryl monomers such as styrene, indene, and vinyl aniline; isobutylene, vinyl acetate, and the like. The copolymer of the present disclosure contains one or more types of structural units derived from (meth)acrylic acid (salt), structural units derived from a sulfonic acid (salt) group-containing monomer, and structural units derived from an ether bond-containing monomer, and may contain one or more types of structural units derived from other monomers as necessary.

[0067] <Physical properties of the copolymer of the present disclosure> The copolymer of the present disclosure preferably has a weight average molecular weight (Mw) of 30,000 or more and 200,000 or less, more preferably 30,000 or more and 150,000 or less, even more preferably 30,000 or more and 100,000 or less, and particularly preferably 30,000 or more and 80,000 or less. By being in the above range, the scale inhibition ability tends to be further improved. Mw may be 30,000 or more and 70,000 or less, or 30,000 or more and 60,000 or less. The Mw of the copolymer of the present disclosure can be measured by the method described in the Examples.

[0068] The copolymer of the present disclosure contains acid groups such as carboxylic acid (salt) groups and sulfonic acid (salt) groups, but the acid groups of the copolymer of the present disclosure may be partially or completely neutralized. The neutralization rate can be calculated, for example, by conventional acid-base titration. The copolymer of the present disclosure may contain structural units derived from a polymerization initiator or a chain transfer agent, such as a hydroxyl group, a sulfonic acid (salt) group, or a hypophosphorous acid (salt) group, at the main chain terminal or the like. In the copolymer of the present disclosure, the content of structural units derived from a sulfonic acid (salt) derived from a polymerization initiator or a chain transfer agent contained in the main chain is preferably 15% by mass or less, more preferably 10% by mass or less, and particularly preferably 6% by mass or less, relative to 100% by mass of the copolymer of the present disclosure.

[0069] [Method for producing the copolymer of the present disclosure] The method for producing the copolymer of the present disclosure is not particularly limited, but it is usually preferable to produce the copolymer by polymerizing structural units derived from (meth)acrylic acid (salt), a sulfonic acid (salt) group-containing monomer, and an ether bond-containing monomer, and, as necessary, other monomers. In the process for producing the copolymer of the present disclosure, a polymerization initiator is usually used. Examples of the polymerization initiator include persulfates such as sodium persulfate, potassium persulfate, and ammonium persulfate, hydrogen peroxide, azo compounds, and peroxides. In the process for producing the copolymer of the present disclosure, it is preferable to use a polymerization solvent and a chain transfer agent. Examples of the chain transfer agent include hydrogen peroxide, hypophosphorous acid (salts) such as sodium hypophosphite, hydrogen sulfite (salts) such as sodium hydrogen sulfite, and mercapto compounds.

[0070] [Uses of the Copolymer of the Present Disclosure] The copolymer of the present disclosure can exhibit high performance in aqueous applications and can be preferably used as a scale inhibitor for use in geothermal power generation processes, oil well and gas well processes, seawater desalination processes or waste liquid concentration processes using forward osmosis membranes or reverse osmosis membranes, boiler water circulation systems, cooling water circulation systems, and the like.

[0071] The copolymer of the present disclosure can be preferably used as a scale inhibitor for, for example, silica scale or calcium carbonate, and is most preferably used as a scale inhibitor for silica scale.

[0072] [Water treatment agent of the present disclosure] The water treatment agent of the present disclosure contains the copolymer of the present disclosure. The water treatment agent of the present disclosure preferably contains the copolymer of the present disclosure at, for example, 1% by mass or more and 70% by mass or less. More preferably, the copolymer is contained at 1 to 50% by mass, particularly preferably 1 to 40% by mass, most preferably 1 to 30% by mass, and most preferably 1 to 20% by mass.

[0073] The water treatment agent of the present disclosure may contain components other than the copolymer of the present disclosure. Examples of components other than the copolymer of the present disclosure include solvents such as water, pH adjusters such as alkalis and acids, oxygen scavengers, anticorrosives, chelating agents, phosphonic acids (salts) such as aminotrimethylenephosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, and salts thereof, carboxyl-containing polymers other than the copolymer of the present disclosure, surfactants, defoamers, pitch control agents, slime control agents, and the like.

[0074] The water treatment chemical of the present disclosure is not particularly limited, but can be preferably used, for example, as a scale inhibitor for preventing scale from occurring in various types of water. The present invention also includes a method for using the copolymer of the present disclosure as a water treatment agent.

[0075] [Scale inhibitor of the present disclosure] The scale inhibitor of the present disclosure contains the copolymer of the present disclosure. The scale inhibitor of the present disclosure preferably contains the copolymer of the present disclosure in an amount of, for example, 10% by mass or more and 100% by mass or less. More preferably, the amount is 20% by mass or more and 70% by mass or less.

[0076] The scale inhibitor of the present disclosure may contain components other than the copolymer of the present disclosure. Examples of components other than the copolymer of the present disclosure include solvents such as water, pH adjusters such as alkalis and acids, oxygen scavengers, anticorrosive agents, chelating agents, phosphonic acids (salts) such as aminotrimethylenephosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, and salts thereof, carboxyl-containing polymers other than the copolymer of the present disclosure, surfactants, defoamers, pitch control agents, slime control agents, and the like.

[0077] The scale inhibitor of the present disclosure is not particularly limited, but can be preferably used as an inhibitor of silica scale or calcium carbonate, for example. The scale inhibitor of the present disclosure is particularly excellent in terms of silica scale inhibition ability, and therefore can be preferably used as a silica scale inhibitor. The present invention also includes a method of using the copolymer of the present disclosure as a scale inhibitor.

[0078] [Uses of the scale inhibitor of the present disclosure] The scale inhibitor of the present disclosure can exhibit high performance in aqueous applications, and can be preferably used as a scale inhibitor for use in geothermal power generation processes, oil well and gas well processes, seawater desalination processes or waste liquid concentration processes using forward osmosis membranes or reverse osmosis membranes, boiler water circulation systems, cooling water circulation systems, etc. The scale inhibitor of the present disclosure can be preferably used as a scale inhibitor for silica scale and calcium carbonate.

[0079] [Scale prevention method of the present disclosure] The scale prevention method of the present disclosure uses the scale inhibitor of the present disclosure or the copolymer of the present disclosure. The scale prevention method of the present disclosure preferably includes a step of adding the scale inhibitor of the present disclosure or the copolymer of the present disclosure to a system to be prevented from scaling. Also, preferably, the method includes a step of controlling the amount of the copolymer of the present disclosure in the system to be prevented from scaling so that it is within a predetermined range. The content of the copolymer of the present disclosure in the system to be prevented from scaling is preferably 0.1 ppm or more and 500 ppm or less, more preferably 1 ppm or more and 300 ppm or less. EXAMPLES

[0080] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0081] <Weight average molecular weight measurement conditions (GPC)> Equipment: Tosoh Corporation HLC8320 Column: SHODEX Asahipak GF-310-HQ, GF-710-HQ, GF-1G-7B manufactured by Showa Denko Corporation Column temperature: 40℃ Flow rate: 0.5ml / min Calibration curve: Polyacrylic acid standard from American Polymer Standards Corporation Eluent: 0.1N sodium acetate

[0082] <Silica scale inhibition rate evaluation test> Preparation of borate buffer solution: 7.420 g of boric acid, 1.753 g of sodium chloride, 19.069 g of sodium borate decahydrate, and ion-exchanged water were added to make a total of 1000 g. Preparation of magnesium aqueous solution: 8.115 g of magnesium sulfate heptahydrate was mixed with ion-exchanged water to make a total of 1000 g. Preparation of an aqueous silica solution: 2.129 g of sodium metasilicate nonahydrate was mixed with ion-exchanged water to make a total of 150 g.

[0083] 1. When testing at a polymer concentration of 50 ppm 73g of pure water and 2g of borate buffer solution were added to the container and stirred. 10g of the above silica aqueous solution, 5g of polymer aqueous solution diluted to 0.1%, and 10g of magnesium aqueous solution were further added while stirring. Then, the mixture was stirred for 18 hours while immersed in a warm bath at 60°C. After 18 hours, the mixture was suction filtered using a polyethersulfone (PES) membrane (manufactured by AS ONE Corporation) with 0.1μm openings. The Si concentration of the obtained filtrate was measured by ICP (optical emission spectroscopy) and converted into SiO2. Silica scale inhibition rate (%) = SiO2 concentration in filtrate (ppm) / SiO2 concentration in feed (ppm) The silica scale inhibition rate was judged according to the following criteria. <Silica scale inhibition rate evaluation criteria> Over 90%: Yes 50% or more but less than 90%: △ Less than 50%: ×

[0084] 2. When testing at a polymer concentration of 60 ppm The evaluation was carried out in the same manner as in the test with a polymer concentration of 50 ppm, except that the amount of pure water added was changed from 73 g to 72 g, and the amount of the 0.1% diluted polymer aqueous solution was changed from 5 g to 6 g.

[0085] <Production Example 1> (1) Synthesis of monomer 370.0 g of n-butyl alcohol and 4.27 g of pellet-shaped sodium hydroxide were charged into a 500 mL capacity four-neck glass flask equipped with a reflux condenser and a stirrer (paddle blade), and the temperature was raised to 60° C. while stirring. Next, 57.0 g of allyl glycidyl ether (hereinafter also referred to as "AGE") was added over 30 minutes, and then the reaction was allowed to proceed for 5 hours. This solution was transferred to a 1,000 mL eggplant flask, and the solvent was removed using a rotary evaporator. 200.0 g of a 20% by mass aqueous sodium chloride solution was added thereto, and the aqueous solution was transferred to a 500 mL separatory funnel, shaken well, and then allowed to stand until separation occurred, and the lower layer was removed. The remaining upper layer was transferred to a 300 mL eggplant flask, and the solvent was removed using a rotary evaporator. The precipitated salt was removed by filtration to obtain a monomer (1). (2) Polymerization In a 1,000 mL glass separable flask equipped with a reflux condenser and a stirrer (paddle blade), 169.2 g of pure water and 0.0168 g of Mohr's salt were charged, and the temperature was raised to 87° C. while stirring to prepare a polymerization reaction system. Next, 253.5 g of an 80% aqueous acrylic acid solution (hereinafter also referred to as "80% AA"), 277.4 g of a 40% aqueous solution of sodium 3-allyloxy-2-hydroxypropanesulfonate (hereinafter also referred to as "40% HAPS"), 12.8 g of monomer (1), 79.1 g of a 15% aqueous solution of sodium persulfate (hereinafter also referred to as "15% NaPS"), and 5.2 g of a 35% aqueous solution of sodium hydrogensulfite (hereinafter also referred to as "35% SBS") were dropped from separate nozzles into the polymerization reaction system maintained at 87° C. under stirring. The drop time of each solution was 180 minutes for 80% AA, 120 minutes for 40% HAPS, 120 minutes for monomer (1), and 170 minutes for 35% SBS. The drop speed of each solution was constant, and each solution was added continuously. For 15% NaPS, the drop speed was 0.30 g / min from 0 to 130 minutes, and 0.58 g / min from 130 to 190 minutes. After the dropwise addition of 15% NaPS was completed, the reaction solution was maintained (aged) at 87° C. for an additional 30 minutes to complete the polymerization. In this manner, polymer (1) of the present disclosure was obtained.

[0086] <Production Example 2> 168.1 g of pure water and 0.0168 g of Mohr's salt were charged into a 1,000 mL glass separable flask equipped with a reflux condenser and a stirrer (paddle blade), and the temperature was raised to 87°C while stirring to prepare a polymerization reaction system. Next, 251.8 g of 80% AA, 275.6 g of 40% HAPS, 12.7 g of monomer (1), 78.6 g of 15% NaPS, and 10.4 g of 35% SBS were dropped from separate nozzles into the polymerization reaction system maintained at 87°C while stirring. The drop times of each solution were 180 minutes for 80% AA, 120 minutes for 40% HAPS, 120 minutes for monomer (1), and 170 minutes for 35% SBS. The drop speed of each solution was constant, and each solution was continuously dropped. The 15% NaPS was added at a drop rate of 0.29 g / min from 0 to 130 minutes, and 0.58 g / min from 130 to 190 minutes. After the dropwise addition of 15% NaPS was completed, the reaction solution was maintained (aged) at 87° C. for an additional 30 minutes to complete the polymerization. In this manner, polymer (2) of the present disclosure was obtained.

[0087] <Production Example 3> 167.4 g of pure water and 0.0168 g of Mohr's salt were charged into a 1,000 mL glass separable flask equipped with a reflux condenser and a stirrer (paddle blade), and the temperature was raised to 87°C while stirring to prepare a polymerization reaction system. Next, 250.9 g of 80% AA, 274.6 g of 40% HAPS, 13.4 g of monomer (1), 78.3 g of 15% NaPS, and 12.6 g of 35% SBS were dropped from separate nozzles into the polymerization reaction system maintained at 87°C under stirring. The drop times of each solution were 180 minutes for 80% AA, 120 minutes for 40% HAPS, 120 minutes for monomer (1), and 170 minutes for 35% SBS. The drop speed of each solution was constant, and each solution was continuously dropped. The 15% NaPS was added at a drop rate of 0.29 g / min from 0 to 130 minutes, and 0.58 g / min from 130 to 190 minutes. After the dropwise addition of 15% NaPS was completed, the reaction solution was maintained (aged) at 87° C. for an additional 30 minutes to complete the polymerization. In this manner, polymer (3) of the present disclosure was obtained.

[0088] <Production Example 4> 135.3 g of pure water and 0.0202 g of Mohr's salt were charged into a 1,000 mL glass separable flask equipped with a reflux condenser and a stirrer (paddle blade), and the temperature was raised to 85°C while stirring to prepare a polymerization reaction system. Next, 291.4 g of 80% AA, 207.3 g of 40% HAPS, 16.2 g of monomer (1), 86.5 g of 15% NaPS, and 17.9 g of 35% SBS were dropped from separate nozzles into the polymerization reaction system maintained at 85°C while stirring. The drop times of each solution were 180 minutes for 80% AA, 120 minutes for 40% HAPS, 120 minutes for monomer (1), and 175 minutes for 35% SBS. The drop speed of each solution was constant, and each solution was continuously dropped. The 15% NaPS was added at a drop rate of 0.32 g / min from 0 to 130 minutes, and 0.64 g / min from 130 to 200 minutes. After the dropwise addition of 15% NaPS was completed, the reaction solution was kept (aged) at 85° C. for an additional 30 minutes to complete the polymerization. In this manner, the polymer (4) of the present disclosure was obtained.

[0089] <Production Example 5> In a 1,000 mL glass separable flask equipped with a reflux condenser and a stirrer (paddle blade), 117.1 g of pure water, 0.0165 g of Mohr's salt, and 13.5 g of paratoluenesulfonic acid (hereinafter also referred to as "PTS") were charged, and the temperature was raised to 87°C while stirring to prepare a polymerization reaction system. Next, 218.8 g of 80% AA, 339.8 g of 40% HAPS, 11.7 g of monomer (1), and 94.1 g of 15% NaPS were dropped from separate nozzles into the polymerization reaction system maintained at 87°C under stirring. The drop time of each solution was 180 minutes for 80% AA, 120 minutes for 40% HAPS, and 120 minutes for monomer (1). The drop speed of each solution was constant, and each solution was continuously dropped. The 15% NaPS was added at a drop rate of 0.35 g / min from 0 to 130 minutes, and 0.69 g / min from 130 to 200 minutes. After the dropwise addition of 15% NaPS was completed, the reaction solution was maintained (aged) at 87° C. for an additional 30 minutes to complete the polymerization. In this manner, polymer (5) of the present disclosure was obtained.

[0090] <Comparative Manufacturing Example 1> In a 1,000 mL glass separable flask equipped with a reflux condenser and a stirrer (paddle blade), 166.7 g of pure water, 0.0165 g of Mohr's salt, and 13.4 g of PTS were charged, and the temperature was raised to 87°C while stirring to prepare a polymerization reaction system. Next, 240.5 g of 80% AA, 175.5 g of 40% HAPS, 42.4 g of monomer (1), 97.1 g of 15% NaPS, and 59.4 g of 35% SBS were dropped from separate nozzles into the polymerization reaction system maintained at 87°C under stirring. The drop times for each solution were 180 minutes for 80% AA, 120 minutes for 40% HAPS, 120 minutes for monomer (1), and 170 minutes for 35% SBS. The drop speed of each solution was constant, and each solution was continuously dropped. The 15% NaPS was added at a drop rate of 0.36 g / min from 0 to 130 minutes, and 0.71 g / min from 130 to 200 minutes. After the dropwise addition of 15% NaPS was completed, the reaction solution was maintained (aged) at 87° C. for an additional 30 minutes to complete the polymerization. In this manner, a comparative polymer (1) was obtained.

[0091] <Comparative Manufacturing Example 2> 253.3g of pure water, 0.0165g of Mohr's salt, and 13.3g of PTS were charged into a 1,000mL glass separable flask equipped with a reflux condenser and a stirrer (paddle blade), and the temperature was raised to 87°C while stirring to prepare a polymerization reaction system. Next, 331.7g of 80% AA, 52.2g of monomer (1), 119.6g of 15% NaPS, and 24.4g of 35% SBS were dropped from separate nozzles into the polymerization reaction system maintained at 87°C under stirring. The drop time of each solution was 180 minutes for 80% AA, 120 minutes for monomer (1), and 170 minutes for 35% SBS. The drop speed of each solution was constant, and each solution was continuously dropped. The 15% NaPS was added at a drop rate of 0.45 g / min from 0 to 130 minutes, and 0.88 g / min from 130 to 200 minutes. After the dropwise addition of 15% NaPS was completed, the reaction solution was maintained (aged) at 87° C. for an additional 30 minutes to complete the polymerization. In this manner, a comparative polymer (2) was obtained.

[0092] <Comparative Manufacturing Example 3> In a glass separable flask with an internal volume of 1500 ml equipped with a paddle impeller (SUS316 paddle-type rotor) stirrer, a reflux condenser, and four dropping devices, 186.4 g of pure water was charged and heated to the boiling reflux temperature. Next, under stirring, 459.1 g of a mixture of 445.1 g of 37% sodium acrylate aqueous solution and 14.0 g of acrylic acid, 299.5 g of 25% HAPS, 33.7 g of 20% NaPS, and 18.3 g of 12.5% ​​aqueous hydrogen peroxide solution were dropped at a constant speed, respectively, over 120 minutes for the mixture of the aqueous sodium acrylate aqueous solution and the aqueous acrylic acid aqueous solution, 120 minutes for the 25% HAPS, 140 minutes for the 20% NaPS, and 120 minutes for the 12.5% ​​aqueous hydrogen peroxide solution. After the dropwise addition, the boiling reflux temperature was maintained for 30 minutes to complete the polymerization. In this way, a comparative polymer (3) was obtained.

[0093] For the polymers obtained in Examples 1 to 5 and Comparative Examples 1 to 3, the silica scale inhibition rates were measured by the above-mentioned method, and the results are shown in Table 1 together with the monomer compositions and weight average molecular weights (Mw) of the polymers.

[0094] [Table 1]

[0095] In Table 1, "monomer composition" indicates the mass % of "structural units derived from acrylic acid (salt) / structural units derived from sulfonic acid (salt) group-containing monomer / structural units derived from ether group-containing monomer," and the silica scale inhibition rate of 50 ppm indicates the test result at a polymer concentration of 50 ppm, and 60 ppm indicates the test result at a polymer concentration of 60 ppm. The results in Table 1 make clear that the (meth)acrylic acid-based copolymer of the present disclosure has good silica suppression ability.

Claims

1. A copolymer comprising a structural unit derived from (meth)acrylic acid (salt), a structural unit derived from a monomer containing a sulfonic acid (salt) group, and a structural unit derived from a monomer containing an ether bond, The structural unit derived from an ether bond-containing monomer is a structural unit derived from a monomer represented by the following general formula (1): The structural unit derived from a sulfonic acid (salt) group-containing monomer is a structural unit derived from a monomer represented by the following general formula (4): A (meth)acrylic acid-based copolymer, in which the content of structural units derived from a sulfonic acid (salt) group-containing monomer relative to 100% by mass of all structural units is 25% by mass or more, and the weight average molecular weight of the copolymer is 30,000 or more and 80,000 or less. 【Chemistry 1】 (In the general formula (1), R 0 represents a hydrogen atom or a methyl group; R 1 represents a CH 2 group, a CH 2 CH 2 group, or a direct bond; one of X and Y represents a hydroxyl group, and the other represents a group represented by the following general formula (2) or a group represented by the following general formula (3).) 【Chemistry 2】 (In the general formulas (2) and (3), R 2 , which may be the same or different, represents an alkylene group having 2 to 4 carbon atoms. n is the average number of moles of oxyalkylene groups (-O-R 2 -) added and represents a number from 0 to 5. R 3 , R 4 , and R 5 each independently represent an alkyl group having 1 to 20 carbon atoms.) 【Chemistry 3】 (In the formula, R 6 represents a hydrogen atom or a methyl group; R 7 represents a CH 2 group, a CH 2 CH 2 group, or a direct bond; R 8 and R 9 represent a hydroxyl group or -SO 3 Z, where Z represents a hydrogen atom, a metal atom, an ammonium group, or an organic amine group; provided that either R 8 or R 9 represents -SO 3 Z, and the other represents a hydroxyl group.)

2. The (meth)acrylic acid-based copolymer according to claim 1, wherein the structural unit derived from the sulfonic acid (salt) group-containing monomer is a structural unit derived from 3-allyloxy-2-hydroxypropanesulfonic acid or a salt thereof.

3. 3. The (meth)acrylic acid-based copolymer according to claim 1 or 2, wherein the content of the structural unit derived from the (meth)acrylic acid (salt) is 15% by mass or more and 74.5% by mass or less, based on 100% by mass of all structural units.

4. The (meth)acrylic acid-based copolymer according to any one of claims 1 to 3, wherein the content of the structural unit derived from the sulfonic acid (salt) group-containing monomer is 25% by mass or more and 60% by mass or less, based on 100% by mass of all structural units.

5. The (meth)acrylic acid-based copolymer according to any one of claims 1 to 4, wherein the content of the structural unit derived from the ether bond-containing monomer is 0.5% by mass or more and 30% by mass or less, based on 100% by mass of all structural units.

6. A water treatment agent comprising the (meth)acrylic acid copolymer according to any one of claims 1 to 5.

7. A scale inhibitor comprising the (meth)acrylic acid copolymer according to any one of claims 1 to 5.

8. A silica scale inhibitor comprising the (meth)acrylic acid copolymer according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • (METH)acrylic acid-based copolymer, method for producing the same and detergent composition using the same

    JP2007231261A

  • Amino group-containing copolymer and method for manufacturing the same

    JP2011116812A

  • Sulfonic acid group-containing polymer, sulfonic acid group-containing monomer, and method for producing them

    JP2012057095A

  • Carboxyl group-containing polymers and compositions thereof

    JP2015522697A

  • Scale inhibitor for geothermal power generation

    JP2016064382A